Online Teaching Self-Efficacy – How English Teachers Feel During the Covid-19 Pandemic - Shzh-chen Nancy Lee; Chie Ogawa (Indonesian TESOL Journal, 2021)
The transition from traditional face-to-face to online teaching during the Covid-19 pandemic happened so rapidly that most teachers started teaching without enough training, preparation, and knowledge of online teaching. In order to better understand this current teaching paradigm, the present research examined how English teachers perceive their own ability to teach online. It investigated English teachers’ self-efficacy to teach online by surveying 138 EFL university teachers in Japan. A survey with 29 Likert-scale and two open-ended questions was developed to examine four latent constructs of online English teaching self-efficacy: technology, pedagogy, communicative language teaching, and self-management. Results of the survey found that English teachers were highly self-efficacious toward teaching online. They were most self-efficacious toward the usage of technology, followed by pedagogy, communicative language teaching (CLT), and least efficacious toward self-management when teaching online. Teachers had high self-efficacy for using different online platforms, organizing group work activities, and conducting formative assessments for evaluation. On the other hand, teachers had lowest self-efficacy for maintaining the balance between research and teaching activities. This paper concludes with some pedagogical implications for English teachers when teaching online.